COMORBIDITY OF GUILLAIN-BARRE SYNDROME AND COVID-19 INFECTION: A CASE REPORT AND A REVIEW OF THE CURRENT LITERATURE - Damjanovic, Radomir (Acta medica Medianae, 2023)
Guillain-Barre syndrome is an immunologically mediated polyradiculoneuropathy characterized by a monophasic course, with a clinical peak within 4 weeks of disease onset. There have been several reports ofGuillain-Barré syndrome, related to COVID-19, days or weeks after the onset of respiratory symptoms. In contrast to that, we describe a case of acute sensorimotor demyelinating polyradiculoneuropathy, followed by COVID-19 infection. Our patient was successfully treated with intravenous immunoglobulins while COVID-19 was treated according to the latest clinical management protocol. In our case, neuropathy symptoms showed aparainfectious profile rather than a post-infectious one, which is uncommon inGuillain-Barré syndrome.
Keywords: Guillain-Barré syndrome (GBS), Coronavirus disease 2019 (COVID-19), weakness